If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8x + 13 = 53 Reorder the terms: 13 + 8x = 53 Solving 13 + 8x = 53 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-13' to each side of the equation. 13 + -13 + 8x = 53 + -13 Combine like terms: 13 + -13 = 0 0 + 8x = 53 + -13 8x = 53 + -13 Combine like terms: 53 + -13 = 40 8x = 40 Divide each side by '8'. x = 5 Simplifying x = 5
| 72=-8(r-2) | | a-b=7 | | 3.7x-8.5=13.7 | | y=-1/4(5)-6 | | 2x^2+27x-7.5=0 | | 6x-2=-32 | | 5=3(x-2)-(x-7) | | 2m+12=3m-21 | | -4a-5=-9 | | 2=(4x-2)(2-x) | | 3x^2+x-9=0 | | -2+4x=10 | | -3(x-4)=57 | | 2x(x+1)+x=1-2x^2 | | 5=-(-z+3) | | 7x-7=4x-7 | | 2(10+n)=48 | | (Y-6)-(y+7)=8y | | 7(p+7)-4(9+p)=12 | | 2.8p=11.2 | | -(x-8)=16 | | 102=-2+8n | | -2-6x=-74 | | 10+9m=55 | | 8z^2-8z+2=0 | | 3(5+a)=-9 | | 12(3x-3)=3(12x+6) | | -176=-8(x+9) | | -4(-2y-5)+5=97 | | 9x^2-28x+20=0 | | -4(5p+2)-47=3(4p+3) | | 3(v-5)=24 |